Modulating the holding time of hardening process in Q-P-T heat treatment: An experimental study on mechanical properties of medium-carbon steel plate - Muhammad, Alief; Prasetiyo, Dani Hari Tunggal; Puspitasari, Poppy (Universitas Muhammadiyah Magelang, 2024)
The metal heat treatment industry has seen substantial growth, with market projections increasing by USD 15.18 billion from 2022 to 2027, driven by advancements in technology. The iron and steel industry significantly contributes to this growth, accounting for six percent of the market share. In this evolving landscape, the Quenching-Partitioning-Tempering (Q-P-T) technique is emerging as a valuable heat treatment process for enhancing Advanced High-Strength Steels (AHSS). The Q-P-T process, involving Quenching, Partitioning, and Tempering, aims to improve the mechanical properties of medium-carbon steels through controlled thermal modifications. This study explores the effects of varying holding times during the Q-P-T treatment on the mechanical properties and microstructure of medium-carbon steel ST60-2. Steel samples were subjected to holding times of 10, 15, and 20 minutes at a temperature of 920°C, followed by quenching to 350°C and partitioning at the same temperature for 15 minutes, with final tempering at 200°C. The results indicate that longer holding times enhance mechanical properties such as Ultimate Tensile Strength (UTS), Product of Strength and Elongation (PSE), and hardness, with the 20-minute sample (Sample 3) achieving the highest UTS of 74.02 kgf/mm² and elongation of 16.63%. Hardness peaked at 109.33 HRB, and improved toughness was observed due to better phase transformation and carbon partitioning (1.36 Joule/mm²). Microstructural analysis revealed finer and more uniformly distributed cementite particles with extended holding times, contributing to enhanced material performance. The findings underscore the potential of Q-P-T heat treatment in optimizing medium-carbon steels, offering a tailored approach for applications requiring superior mechanical properties.